Inkulturasi Liturgi Gereja Bethel Indonesia - Naftali Untung; Priskila Issak Benyamin; Yogi Mahendra (Badan Musyawarah Perguruan Tinggi Keagamaan Kristen Indonesia, 2021)
Liturgical and cultural inculturation is an important part of worship in the context of the church in Indonesia. This interest arises because the church is entering a post-modern era where local culture has not experienced inculturation, but post-modern culture has entered to change the church's thinking. Until now, the Bethel Indonesia church has not comprehensively carried out the process of inculturation of the liturgy and culture. From this fact, it is necessary to develop and put forward a comprehensive inculturation process by the church today so as not to be trapped by the syncretism of Indonesian local culture and the rise of post-modern culture. The purpose of this study is to find out the importance of the process, how the process and the impact of inculturation are truly in accordance with the Indonesian context. In revealing the liturgical and cultural inculturation in the church today, the author uses a qualitative descriptive research method. The results of the study indicate that the inculturation process really has an impact on the congregation in interpreting Christian values and enthusiasm for prayer and worship. Inculturation has succeeded in bringing about a different experience when worshiping compared to a liturgy that is carried out routinely with the same stages of worship from week to week.AbstrakInkulturasi liturgi dan budaya adalah bagian penting dalam peribadatan dalam konteks gereja di Indonesia. Kepentingan ini muncul karena gereja sedang memasuki masa post-modern dimana kebudayaan lokal belum mengalami inkulturasi, tetapi budaya post-modern sudah masuk untuk mengubah pemikiran gereja. Hingga saat ini, gereja Bethel Indonesia belum secara komprehensif melakukan proses inkulturasi liturgi dan budaya itu. Dari kenyataan ini, maka perlu dikembangkan dan dikedepankan proses inkulturasi secara menyeluruh oleh gereja masa kini supaya tidak terjebak dengan sinkritisme budaya lokal Indonesia dan maraknya budaya post-modern. Tujuan dari penelitian ini adalah untuk mendapatkan pentingnya proses, bagaimana proses dan dampak inkulturasi yang benar sesuai dengan konteks Indonesia. Dalam mengungkapkan inkulturasi liturgi dan budaya pada gereja masa kini tersebut, penulis menggunakan metode penelitian kualitatif deskriptif. Hasil penelitian menunjukkan bahwa proses inkulturasi yang benar memberikan dampak kepada jemaat dalam memaknai nilai-nilai Kekristenan dan semangat dalam berdoa dan beribadah. Inkulturasi berhasil membawa umat merasakan suatu pengalaman yang berbeda ketika beribadah dibandingkan dengan sesuatu liturgi yang dilakukan secara rutin dengan tahapan ibadah yang sama dari minggu ke minggu.